The beginnings of nursing in Mexico: Conflicts of power and gender, 1896-1904 - Douglas C. Nance (Universidad de Alicante, 2018)
At the beginning of secular nursing in Mexico the career was involved in conflicts of power, role and gender with medicine. Objective: This article explores the beginnings of nursing education in Mexico from a historical and epistemological perspective with a focus on power, role and gender. Method: Primary sources have been used from the Historical Archive of the Ministry of Health of Mexico and Columbia University of New York and Mexican nursing journals, among others. Results: The first directors-nurses in Mexico from 1896 to 1904, North American and British-American, were not submissive to doctors, which resulted in conflicts. The nursing school and the hospital have had a patriarchal environment where the "good" nurse has promoted the feminine values of piety, purity, submission and domesticity, resulting in the submission of the nurse and the exclusion of men. Conclusions: Organized Mexican medicine only accepted those who know how to obey and submit. The result was the segregation of the nurse to a subordinate position. These conflicts and their results were definitive in the path that Mexican nursing would take.